Microstructures: Autonomous Magnetic Microrobots by Navigating Gates for Multiple Biomolecules Delivery (Small 25/2018). Issue 25 (21st June 2018) - Hu, Xinghao; Lim, Byeonghwa; Torati, Sri Ramulu; Ding, Junjia; Novosad, Valentine; Im, Mi‐Young; Reddy, Venu; Kim, Kunwoo; Jung, Eunjoo; Shawl, Asif Iqbal; Kim, Eunjoo; Kim, CheolGi
Abstract : In article number 1800504, Valentine Novosad, CheolGi Kim, and co‐workers report a universal micromagnet junction of self‐navigating gates for autonomous microrobotic carriers to deliver biomolecules to specific sites using a remote magnetic field. The non‐magnetic gap between the lithographically fabricated donor and acceptor micromagnets creates a crucial energy barrier to regulate carrier particle gating. The proposed junctions could lead to a novel lab‐on‐chip microfluidic platform for the synchronous digital transport, manipulation and sorting of bioconjugated nanoparticles and cells.